Proteção judicial efetiva: uma constante preocupação com o tempo (mas, também, com a qualidade) - Gonçalves, José Wilson (2016)
The deep concern about the abyss between the academy and the practice in which the Law is established has encouraged the inception of this work, which gives special emphasis to the prohibition of insufficient judicial protection, mainly due to abnormal delay and poor quality of the Lawsuit as a public service. Therefore, it was entitled "Effective judicial protection - A constant concern about time (but also with quality)." It is essential that, intransigently, an adequate speed is given to the lawsuit, specifically taking into account the need for the holder of the right defended in court. For this constitutional desideratum to be achieved, it is imperative to start with a good law including a good judicial structure and good applicators. They embody a trilogy which must work as a necessarily tuned gear. In addition, the process can not be regarded as a pure logical order, inflexibly subject to predetermined formulas, but instead, it must be practiced in a sensitive way to the specificity which justifies it democratically, rendering the service particularly appropriate, and always observing the useful contradictory, prior or postponed. In this respect, the differentiated procedures are honored, precisely aiming to meet the concrete need, especially the procedures established in order to tutor the right from the outset, either for the sake of assertion or for satisfaction, either in case of urgency or in case of evidence, fighting against scientific treasures or baroque formalism. The main idea is to draw attention to the fact that the study of law must be committed to a practical result, never allowing it to be conceived as a fuel of intellectual vanity, highly harmful